Effect of a Blend of Zingiber officinale Roscoe and Bixa orellana L. Herbal Supplement on the Recovery of Delayed-Onset Muscle Soreness Induced by Unaccustomed Eccentric Resistance Training: A Randomized, Triple-Blind, Placebo-Controlled Trial - Dominguez-Balmaseda, Diego; Diez-Vega, Ignacio; Larrosa, Mar; San Juan, Alejandro F.; Issaly, Nicolas; Moreno-Pérez, Diego; Burgos, Silvia; Sillero-Quintana, Manuel; Gonzalez, Cristina; Bas, Andrea; Roller, Marc; Pérez-Ruiz, Margarita (Frontiers in Physiology, 2020)
Background: there is an increasing interest in the use of eccentric muscle exercise to improve physical condition, especially with regards to its health-related benefits. However, it is known that unaccustomed eccentric exercise causes muscle damage and delayed pain, commonly defined as "delayed onset muscle soreness" (DOMS). The efficacy of herbal preparations in subjects suffering from DOMS has been reported in a few previous studies with small or moderate outcome measures related to muscle recovery. The present study aimed to evaluate the effects of a polyherbal mixture containing whole Zingiber officinale Roscoe and Bixa orellana L., powders called ReWin(d) in young male athletes suffering from DOMS induced by a 1-hour session of plyometric exercises. Methods: Thirty-three young male athletes participated in this randomized, double-blind, placebo-controlled trial, 17 of them assigned to the Rewin(d) group and 16 of them to the Placebo group. Creatine kinase (CK) was measured as a muscle damage marker, pain was assessed using the Visual Analog Scale (VAS), muscle performance was measured through half-squat exercise (HS) monitored with an accelerometer (Encoder) and Heart rate variability (HRV) was monitored for 5 minutes with the subjects in the supine position. All determinations were performed before and after the eccentric session and 24, 48 and 72 hours after the session. Results: the eccentric exercise session caused an increase of CK at 24h and 48h after exercise intervention in both groups (p<0.001). There was no interaction between groups regarding muscle damage. The pain increased after the training session in both groups (p<0.001) and a significant interaction was observed between groups at 48h after exercise (p=0.004). Lower limb muscular power showed a significant interaction between groups 24 hours after exercise (p=0.049), the Placebo group showed a reduction in muscle power compared to the Rewin(d) group. The LF/HF ratio decreased significantly at 72 h after exercise in the herbal group but not in the Placebo group. Conclusions: the herbal supplement maintained the maximum power of the lower limbs and attenuated muscle pain